Influence of Cultivar on the Postharvest Hardening of Trifoliate Yam (Dioscorea dumetorum) Tubers - Christian Siadjeu; Emmanuel Akdowa Panyoo; Gabriel Mahbou Somo Toukam; Joseph Martin Bell; Benoit Nono; Gabriel Nama Medoua (Advances in Agriculture)
The influence of cultivar on the postharvest hardening of Dioscorea dumetorum tubers was assessed. 32 cultivars of D. dumetorum tubers were planted in April 2014, harvested at physiological maturity, and stored under prevailing tropical ambient conditions (19–28°C, 60–85% RH) for 0, 5, 14, 21, and 28 days. Samples were evaluated for cooked hardness. Results showed that one cultivar, Ibo sweet 3, was not affected by the hardening phenomenon. The remaining 31 were all subject to the hardening phenomenon at different degree. Cooked hardness increased more rapidly in cultivars with many roots on the tuber surface compared to cultivars with few roots on the tuber surface. When both the characteristics flesh colour and number of roots on tuber surface were associated, cooked hardness in cultivars with yellow flesh and many roots increased more rapidly than in cultivars with white flesh and many roots, whereas cooked hardness in cultivars with yellow flesh and few roots increased more slowly than in cultivars with white flesh and few roots. Accessions collected in high altitude increased more rapidly compared to accessions collected in low altitude. The cultivar Ibo sweet 3 identified in this study could provide important information for breeding program of D. dumetorum against postharvest hardening phenomenon.